I implemented three of the four De Morgan's Laws in Haskell: notAandNotB :: (a -> c, b -> c) -> Either a b -> c notAandNotB (f, g) (Left x) = f x notAandNotB (f, g) (Right y) = g y notAorB :: (Either a b -> c) -> (a -> c, b -> c) notAorB f = (f . Left, f . Right) notAorNotB :: Either (a -> c) (b -> c) -> (a, b) -> c notAorNotB (Left f) (x, y) = f x notAorNotB (Right g) (x, y) = g y However, I don't suppose that it's possible to implement the last law (which has two inhabitants): notAandBLeft :: ((a, b) -> c) -> Either (a -> c) (b -> c) notAandBLeft f = Left (\a -> f (a, ?)) notAandBRight :: (